Interrelation of Hadith and Javanese Culture in the Translation of Hadith Kasyf al-Liṡām fi Tarjamati Bulūgh al-Marām by KH. Misbah Mustafa - Sakinah, Fatihatus; Rodliyatuz Zahro' (Taqaddumi: Journal of Quran and Hadith Studies, 2024)
The presence of hadith translations in Indonesia shows the reading and understanding of the Prophet's hadith, as well as a concrete form of the meeting between the world of texts, namely hadith and the concrete world of readers. This meeting emphasizes the existence of a cultural process. This study aims to read the dialectic of hadith with local and social culture in the translation of the hadith Kasyf al-Liṡāmfi Tarjamati Bulugh al-Maram fi Tarjamati Bulugh al-Maram. This study is library research with an inductive method and with a historical-critical approach. The results of this study indicate that the interrelation between hadith and culture in the translation of the hadith Kasyf al-Liṡāmfi Tarjamati Bulugh al-Maram is explained through two patterns, namely adaptation and integration. The adaptation pattern is seen in the use of local language (Javanese) and socio-cultural (pesantren) which reflects respect for communication. The integration pattern is shown in the explanation of hadith material in the local Javanese context through the reconstruction of his life experiences in the surrounding community. Interrelation reflects the uniqueness of hadith translation in the archipelago as a depiction of the dynamic dialogue between Islamic teachings and local cultural diversity.